Academic capital and institutional stratification: determinants of graduate success in Moroccan higher education - Youness Ezzaaime; Said Maizzou; Ali Raigat; Abdeljabbar Abdouni (Institute of Advanced Engineering and Science, 2026)
In spite of the massification of higher education after the implementation of the licence–master–doctorate (LMD) reform, the graduation rates from open-access faculties stay low (under 30%), and the factors driving these low performance rates are not well understood. This study attempts to explain factors influencing the stratification of academic achievement of students graduating from Hassan I University (2012–2017), through the analysis of the three factors: pre-university academic capital, institutional selectivity, and socioeconomic resources. On the baccalaureate grade, we use ordinary least squares (OLS) regression, analysis of variance (ANOVA), t-tests, and chi-square analyses to find that it is the strongest predictor with β = 0.481 and r = 0.595 (p < 0.001), which is better than international benchmarks. The segregation effect by institution is the highest among the groups’ effects, with selective institutions having an effect of over 2.5 grade points (when controlling for student inputs), indicated by the large group effect (η2 = 0.275). Receipt of scholarships is a positive predictor of performance (β = 0.213 with p = 0.031); the employment in term-time is selected. 45.9% of grade variance is accounted for by the full model. We believe that academic disparities stem from secondary schooling and is exacerbated by disparities in faculty quality in the open market, and therefore secondary faculty preparation and open-access faculty resources must be addressed.